Synthesis and Characterization of Tulipalin-Based Polymers - Lee1, Chanwoo; Song2, Kyunghun (Asian Journal of Chemistry, 2014)
2-Hydroxyethyl methacrylate (HEMA) terminated poly(DL-lactide) macromonomers (HEMA-PDLLA) were synthesized and copolymerized with a-methylene-g-butyrolactone (MBL) to produce their graft copolymers of poly(tulipalin A) (PT) and poly(DL-lactide) (PDLLA) (PT-g-PDLLA). HEMA-PDLLA were synthesized by ring opening polymerization (ROP) of DL-lactide in the presence of 2-hydroxyethyl methacrylate. The thermal stabilities of PT-g-PDLLA copolymers were investigated by Thermogravimetry analysis. There were two stages in weight loss of each copolymer by recorded at 270-300 ºC are attributed to the decomposition of poly(DL-lactide). Two isolated Tg were shown in each case, corresponding to the poly(DL-lactide)-rich domain and PT-rich domain were also investigated by differential scanning calorimetry.